Preparation method of carbon nanotube / polyether-ether-ketone composite material

Through the treatment methods of sulfonation and hydroxyl modification, the agglomeration and winding problems of carbon nanotubes and polyether ether ketone composite materials are solved during composite, achieving uniform dispersion and chemical bond connection of the material, significantly improving its mechanics and flame retardant Performance expands the scope of application.

CN119119504APending Publication Date: 2024-12-13厦门华碳科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411384238.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Carbon nanotubes and polyether ether ketone resin are prone to agglomeration and wrapping when combined, resulting in poor dispersion and stability, which cannot meet the application needs of high-performance materials.

Method used

By sulfonating treatment of polyether ether ketone and hydroxy-modified single-wall carbon nanotubes, chemical bond connections are formed, and combined with the hot pressing molding method, uniform dispersion of the material and structural tightness are achieved, and mechanical properties and flame retardant properties are enhanced.

Benefits of technology

The mechanical properties, friction resistance, flame retardant properties and thermal stability of carbon nanotube/polyether ether ketone composites have been improved, and the application fields of polyether ether ketones have been broadened, and the production costs have been reduced and production efficiency has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119504A_ABST
    Figure CN119119504A_ABST
Patent Text Reader

Abstract

According to the preparation method of the carbon nanotube / polyether-ether-ketone composite material provided by the invention, the single-walled carbon nanotube is added into a polyether-ether-ketone matrix as a functional filler, and the interior of the material is more compact by adopting a hot press molding method, so that the stability of the material structure is improved. Besides, the hydroxyl is utilized to modify the single-walled carbon nanotubes, aggregation and winding of the single-walled carbon nanotubes in the sulfonated polyetheretherketone are reduced, and the two substances are connected through chemical bonds, so that uniform dispersion of the two substances in the composite material is promoted. The carbon nano tube is used as a nano filler, so that the thermal decomposition speed of the polyether-ether-ketone is effectively slowed down, the thermal stability of the material is improved, and meanwhile, the mechanical and flame-retardant properties of the polyether-ether-ketone composite material are also enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and in particular to a method for preparing a carbon nanotube / polyetheretherketone composite material. Background Art

[0002] Polyetheretherketone (PEEK) is a semi-crystalline thermoplastic polymer, the molecular chain contains rigid benzene rings, flexible ether bonds and carbonyl groups that promote intermolecular forces. PEEK has excellent wear resistance, electrical insulation, radiation resistance, chemical stability, biocompatibility, thermal stability, good flame resistance, low smoke generation, and is reusable with a high recycling rate. PEEK has outstanding mechanical properties and dimensional stability at high temperatures, so it is widely used in aviation, automobile manufacturing, industry, electronics and other fields, and is often used as a metal substitute. However, pure polyetheretherketone resin has disadvantages such as poor shear performance, high brittleness, and low operating temperature, which greatly limits its scope of application.

[0003] Single-walled carbon nanotubes are one-dimensional tubular structures formed by rolling up flake graphite layers. Single-walled carbon nanotubes are considered to be ideal nano-scale reinforcing agents and flame retardants due to their unique mechanical properties, aspect ratio and nanometer size, and exhibit excellent thermal, electrical and corrosion resistance properties. Although carbon nanotubes have excellent properties, they are prone to agglomeration and have weak interface bonding with the matrix in practical applications.

[0004] With the rapid progress of the manufacturing industry, the operating speed and load-bearing capacity of power machinery have gradually increased. A single polymer material can no longer meet the diverse use requirements in terms of load-bearing capacity, friction and wear, flame retardancy and other properties. Therefore, in order to optimize its comprehensive performance, material composite is considered to be the most effective solution. However, when carbon nanotubes are composited with polyetheretherketone resin, they are prone to agglomeration and entanglement, and have problems such as poor dispersion and stability, resulting in poor comprehensive performance of the composite material and unable to meet application requirements. Summary of the invention

[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a method for preparing a carbon nanotube / polyetheretherketone composite material. Through the preparation method, the effective combination of polyetheretherketone and single-walled carbon nanotubes is achieved, and the prepared composite material has excellent mechanical properties, friction properties and flame retardant properties.

[0006] In order to achieve the above object, the present application provides a method for preparing a carbon nanotube / polyetheretherketone composite material, comprising the following steps:

[0007] (1) Sulfonation of polyetheretherketone;

[0008] (2) Hydroxyl-modified single-walled carbon nanotubes;

[0009] (3) Synthesis of carbon nanotube / polyetheretherketone composites.

[0010] In any embodiment, the sulfonation treatment of the polyetheretherketone is as follows: after the polyetheretherketone is dissolved in concentrated sulfuric acid at 20-30°C and stirred, the reaction solution is poured into a certain volume of ice water, and the stirring is continued for 2-3 hours, followed by standing for 24-36 hours; the precipitate is then washed and filtered with deionized water for multiple times; finally, the precipitate is dried to obtain the sulfonated polyetheretherketone.

[0011] In any embodiment, the pH value of the aqueous solution for washing the precipitate is neutral.

[0012] In any embodiment, the mass fraction of the concentrated sulfuric acid is 95% to 98%, and the stirring time is 24 to 76 hours.

[0013] In any embodiment, the hydroxyl-modified single-walled carbon nanotubes are specifically prepared by the following steps: adding the single-walled carbon nanotubes to 100 mL of a mixed solution at a temperature of 60 to 80° C., and stirring with a magnetic stirrer for 6 to 10 hours; after centrifugation, washing with distilled water for 3 to 5 times, washing with ethanol for 2 to 3 times, and drying at 80 to 100° C. for 12 hours to obtain hydroxylated single-walled carbon nanotubes.

[0014] In any embodiment, the mixed solution is a mixture of H2O2 and concentrated sulfuric acid in a volume ratio of 3:7.

[0015] In any embodiment, the synthesis of the carbon nanotube / polyetheretherketone composite material includes: ultrasonically dispersing a certain amount of sulfonated PEEK powder in anhydrous ethanol to fully infiltrate the sulfonated PEEK and then stirring to prepare a sulfonated PEEK suspension; ultrasonically dispersing hydroxylated single-walled carbon nanotubes in anhydrous ethanol, and then dropwise adding the dispersion into the sulfonated PEEK suspension for premixing; drying the resulting mixed solution at 120-150°C for 4-6 hours to remove the solvent; hot pressing in a stainless steel mold, and then cooling and demolding at room temperature to obtain a composite material block.

[0016] In any embodiment, the temperature of the hot pressing molding is 380-400° C., the pressure is 10-15 MPa, and the holding time is 10-20 min.

[0017] In any embodiment, the amount of hydroxylated single-walled carbon nanotubes added is 1%-7%.

[0018] Preferably, the added amount of hydroxylated single-walled carbon nanotubes is 1%, 3%, 5%, or 7%.

[0019] Beneficial effects of the present invention:

[0020] 1) The present invention utilizes hydroxyl-modified single-walled carbon nanotubes to reduce the aggregation and entanglement of single-walled carbon nanotubes in sulfonated polyetheretherketone, and the two substances are connected by chemical bonds, thereby promoting their uniform dispersion in the composite material. The hot pressing method is further adopted to make the interior of the material more compact, improve the stability of the material structure, thereby enhancing the mechanical properties, friction resistance, chemical corrosion resistance and flame retardancy of the composite material, and broaden the application field of polyetheretherketone.

[0021] 2) PEEK is a main chain composed of carbonyl, ether bond and aromatic ring, and can withstand high temperature up to 300°C; carbon nanotubes as nanofillers can improve the melting performance of polymers close to the ignition temperature, effectively slow down the thermal decomposition rate of PEEK, delay the initial decomposition temperature of PEEK, and improve the thermal stability of the material. Therefore, carbon nanotube / PEEK composites have excellent performance in flame retardancy.

[0022] 3) The present invention connects sulfonated polyetheretherketone and hydroxylated single-walled carbon nanotubes through a grafting reaction, and the two are connected together in the form of chemical bonds to form chemical bonds, so that the composite material is more uniform, and the mechanical properties of the polyetheretherketone composite material are effectively improved, and the comprehensive performance is improved. The addition of 5wt% modified carbon nanotubes can increase the bending strength of the composite material to 219.84MPa; and the preparation steps of the sulfonation of polyetheretherketone and the hydroxylation of carbon nanotubes of the present invention are few and the process is simple, which saves costs and improves production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 An emission electron microscope image of the hydroxylated single-walled carbon nanotubes in this application;

[0024] Figure 2 is a heat release rate curve of the carbon nanotube / polyetheretherketone composite material in this application;

[0025] Figure 3 This is a physical picture of the carbon residue after the cone weight test of the carbon nanotube / polyetheretherketone composite material in this application. DETAILED DESCRIPTION

[0026] Hereinafter, the embodiment of the method for preparing the carbon nanotube / polyetheretherketone composite material of the present application is specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0027] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0028] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0029] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0030] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0031] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0032] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0033] A method for preparing a carbon nanotube / polyetheretherketone composite material comprises the following steps:

[0034] (1) Preparation of sulfonated polyetheretherketone;

[0035] (2) Preparation of hydroxyl-modified single-walled carbon nanotubes;

[0036] (3) Preparation of carbon nanotube / polyetheretherketone composite materials.

[0037] In one embodiment of the present application, the specific process for preparing sulfonated polyetheretherketone in step (1) includes:

[0038] After polyetheretherketone is dissolved in concentrated sulfuric acid at 20-30°C and stirred, the reaction solution is poured into a certain volume of ice water, stirred for 2-3 hours, and then allowed to stand for 24-36 hours. The precipitate is washed and filtered with deionized water for many times until the pH value of the washing water solution is neutral. Finally, the precipitate is dried to obtain sulfonated polyetheretherketone.

[0039] Under the temperature condition of 20-30°C, polyetheretherketone and its solvent and other components have good stability and are not easy to degrade or have other adverse reactions, which helps to maintain the stability of the reaction system and improve the selectivity and yield of the sulfonation reaction.

[0040] Ice water is used to lower the reaction temperature and control the occurrence of side reactions; after the sulfonation is completed, the sulfonation liquid is added to water and appropriately diluted, and the sulfuric acid compound can be precipitated.

[0041] After sulfonation, the purpose of washing to neutrality is to remove residual acid, making the material more stable and pure, which helps to ensure the quality and reliability of the final product. If the residual acid is not completely removed, it may have a negative impact on its further processing steps.

[0042] In one embodiment of the present application, the specific process of preparing the hydroxyl-modified single-walled carbon nanotubes in step (2) includes:

[0043] Add the single-walled carbon nanotubes to 100 mL of a mixed solution at 60-80°C, stir with a magnetic stirrer for 6-10 hours, centrifuge and wash with distilled water for 3-5 times, centrifuge and wash with ethanol for 2-3 times, and dry at 80-100°C for 12 hours to obtain hydroxylated single-walled carbon nanotubes.

[0044] In one embodiment of the present application, the specific process of preparing the carbon nanotube / polyetheretherketone composite material in step (3) includes: ultrasonically dispersing a certain amount of sulfonated PEEK powder in anhydrous ethanol to fully infiltrate the sulfonated PEEK and then stirring to prepare a sulfonated PEEK suspension; ultrasonically dispersing hydroxylated single-walled carbon nanotubes in anhydrous ethanol, and then dropwise adding the dispersion into the sulfonated PEEK suspension for premixing; drying the resulting mixed solution at 120-150°C for 4-6 hours to remove the solvent; hot pressing in a stainless steel mold at a temperature of 380-400°C, a pressure of 10-15MPa, and a holding time of 10-20min, and then cooling and demolding at room temperature to obtain a composite material block.

[0045] Disperse the single-walled carbon nanotubes in 500-800 ml of ethanol and ultrasonicate for 40-50 minutes. The ultrasonic dispersion time should be long enough to ensure full dispersion. However, too long ultrasonication time may cause damage to the carbon nanotubes or other adverse effects.

[0046] The dispersion was slowly added dropwise to ensure full reaction.

[0047] The temperature, pressure and holding time of hot pressing are very important process parameters, which have a direct impact on the quality and performance of the molded products.

[0048] Too high a temperature may cause the plastic to melt excessively, resulting in appearance defects in the molded product. Too high a temperature may also cause dimensional deviations in the molded product, because the plastic expands more at high temperatures, causing the size of the molded product to exceed the design requirements; too low a temperature may cause the plastic to not melt completely, resulting in insufficient density of the molded product, and prone to defects such as holes and bubbles.

[0049] Too high pressure may cause destructive defects such as indentations and scratches on the surface of the molded product. Too low pressure may cause the density of the molded product to be insufficient, and defects such as roughness and bubbles may easily appear.

[0050] Too long a holding time may lead to a long molding cycle, reducing production efficiency. Too long a holding time may also cause thermal aging of the molded product, resulting in a decrease in the performance of the molded product; too short a holding time may lead to insufficient density of the molded product, which may easily lead to defects such as holes and bubbles.

[0051] In one embodiment of the present application, the mass fraction of concentrated sulfuric acid in step (1) is 95% to 98%, and the stirring time is 24 to 76 hours.

[0052] The sulfonation reaction rate is related to the water content of concentrated sulfuric acid. The sulfonation reaction rate is inversely proportional to the square of the water concentration, that is, the more water there is in the reaction system, the faster the reaction rate decreases. Therefore, high-concentration concentrated sulfuric acid is selected. The time is related to the degree of sulfonation. The longer the reaction time, the higher the degree of sulfonation, the better the ionic conductivity of the material, but it will lead to a decrease in mechanical properties.

[0053] In one embodiment of the present application, the mixed solution in step (2) is a mixture of H2O2 and concentrated sulfuric acid in a volume ratio of 3:7.

[0054] A mixture of H2O2 and concentrated sulfuric acid in a volume ratio of 3:7 is called piranha solution, also known as piranha etching solution. This mixture has strong oxidizing properties, causing hydroxylation on the surface of the material.

[0055] In one embodiment of the present application, the amount of hydroxylated single-walled carbon nanotubes added in step (3) is 1%, 3%, 5%, or 7%.

[0056] Example

[0057] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0058] Example 1

[0059] A method for preparing a carbon nanotube / polyetheretherketone composite material comprises the following steps:

[0060] (1) Preparation of sulfonated polyetheretherketone:

[0061] 10g of polyetheretherketone was dissolved in 500ml of 98% concentrated sulfuric acid at 30°C, stirred for 48h, and then poured into 10 times the volume of ice water, stirred for 3h, and then allowed to stand for 36h. The precipitate was washed and filtered with deionized water several times until the pH value of the washing water solution was neutral. Finally, the precipitate was dried to obtain sulfonated polyetheretherketone.

[0062] (2) Preparation of hydroxyl-modified single-walled carbon nanotubes:

[0063] The single-walled carbon nanotubes were added to 100 mL of a mixed solution (the volume ratio of H2O2 and concentrated sulfuric acid was 3:7) at 80°C, and stirred with a magnetic stirrer for 8 hours. After centrifugation, the solution was washed 5 times with distilled water, 3 times with ethanol, and dried at 80°C for 12 hours to obtain hydroxylated single-walled carbon nanotubes.

[0064] (3) Preparation of carbon nanotube / polyetheretherketone composite materials:

[0065] The sulfonated PEEK powder is ultrasonically dispersed in anhydrous ethanol to fully infiltrate the sulfonated PEEK and then stirred to prepare a sulfonated PEEK suspension; hydroxylated single-walled carbon nanotubes with an addition ratio of 1% are ultrasonically dispersed in anhydrous ethanol, and then the dispersion is dropped into the sulfonated PEEK suspension for premixing; the obtained mixed solution is dried at 150°C for 4h to remove the solvent; hot pressing is performed in a stainless steel mold at a temperature of 380°C, a pressure of 10MPa, and a holding time of 10min, and then cooled and demolded at room temperature to obtain a composite material block.

[0066] Example 2

[0067] A method for preparing a carbon nanotube / polyetheretherketone composite material comprises the following steps:

[0068] (1) Preparation of sulfonated polyetheretherketone:

[0069] 10g of polyetheretherketone was dissolved in 500ml of 98% concentrated sulfuric acid at 30°C, stirred for 48h, and then poured into 10 times the volume of ice water, stirred for 3h, and then allowed to stand for 36h. The precipitate was washed and filtered with deionized water several times until the pH value of the washing water solution was neutral. Finally, the precipitate was dried to obtain sulfonated polyetheretherketone.

[0070] (2) Preparation of hydroxyl-modified single-walled carbon nanotubes:

[0071] The single-walled carbon nanotubes were added to 100 mL of a mixed solution (the volume ratio of H2O2 and concentrated sulfuric acid was 3:7) at 80°C, and stirred with a magnetic stirrer for 8 hours. After centrifugation, the solution was washed 5 times with distilled water, 3 times with ethanol, and dried at 80°C for 12 hours to obtain hydroxylated single-walled carbon nanotubes.

[0072] (3) Preparation of carbon nanotube / polyetheretherketone composite materials:

[0073] The sulfonated PEEK powder is ultrasonically dispersed in anhydrous ethanol to fully infiltrate the sulfonated PEEK and then stirred to prepare a sulfonated PEEK suspension; 3% of hydroxylated single-walled carbon nanotubes are ultrasonically dispersed in anhydrous ethanol, and then the dispersion is dropped into the sulfonated PEEK suspension for premixing; the obtained mixed solution is dried at 150°C for 4h to remove the solvent; hot pressing is performed in a stainless steel mold at a temperature of 380°C, a pressure of 10MPa, and a holding time of 10min, and then cooled and demolded at room temperature to obtain a composite material block.

[0074] Example 3

[0075] A method for preparing a carbon nanotube / polyetheretherketone composite material comprises the following steps:

[0076] (1) Preparation of sulfonated polyetheretherketone:

[0077] 10g of polyetheretherketone was dissolved in 500ml of 98% concentrated sulfuric acid at 30°C, stirred for 48h, and then poured into 10 times the volume of ice water, stirred for 3h, and then allowed to stand for 36h. The precipitate was washed and filtered with deionized water several times until the pH value of the washing water solution was neutral. Finally, the precipitate was dried to obtain sulfonated polyetheretherketone.

[0078] (2) Preparation of hydroxyl-modified single-walled carbon nanotubes:

[0079] The single-walled carbon nanotubes were added to 100 mL of a mixed solution (the volume ratio of H2O2 and concentrated sulfuric acid was 3:7) at 80°C, and stirred with a magnetic stirrer for 8 hours. After centrifugation, the solution was washed 5 times with distilled water, 3 times with ethanol, and dried at 80°C for 12 hours to obtain hydroxylated single-walled carbon nanotubes.

[0080] (3) Preparation of carbon nanotube / polyetheretherketone composite materials:

[0081] The sulfonated PEEK powder is ultrasonically dispersed in anhydrous ethanol to fully infiltrate the sulfonated PEEK and then stirred to prepare a sulfonated PEEK suspension; 5% of hydroxylated single-walled carbon nanotubes are ultrasonically dispersed in anhydrous ethanol, and then the dispersion is dropped into the sulfonated PEEK suspension for premixing; the obtained mixed solution is dried at 150°C for 4h to remove the solvent; hot pressing is performed in a stainless steel mold at a temperature of 380°C, a pressure of 10MPa, and a holding time of 10min, and then cooled and demolded at room temperature to obtain a composite material block.

[0082] Example 4

[0083] A method for preparing a carbon nanotube / polyetheretherketone composite material comprises the following steps:

[0084] (1) Preparation of sulfonated polyetheretherketone:

[0085] 10g of polyetheretherketone was dissolved in 500ml of 98% concentrated sulfuric acid at 30°C, stirred for 48h, and then poured into 10 times the volume of ice water, stirred for 3h, and then allowed to stand for 36h. The precipitate was washed and filtered with deionized water several times until the pH value of the washing water solution was neutral. Finally, the precipitate was dried to obtain sulfonated polyetheretherketone.

[0086] (2) Preparation of hydroxyl-modified single-walled carbon nanotubes:

[0087] The single-walled carbon nanotubes were added to 100 mL of a mixed solution (the volume ratio of H2O2 and concentrated sulfuric acid was 3:7) at 80°C, and stirred with a magnetic stirrer for 8 hours. After centrifugation, the solution was washed 5 times with distilled water, 3 times with ethanol, and dried at 80°C for 12 hours to obtain hydroxylated single-walled carbon nanotubes.

[0088] (3) Preparation of carbon nanotube / polyetheretherketone composite materials:

[0089] The sulfonated PEEK powder is ultrasonically dispersed in anhydrous ethanol to fully infiltrate the sulfonated PEEK and then stirred to prepare a sulfonated PEEK suspension; 7% of hydroxylated single-walled carbon nanotubes are ultrasonically dispersed in anhydrous ethanol, and then the dispersion is dropped into the sulfonated PEEK suspension for premixing; the obtained mixed solution is dried at 150°C for 4h to remove the solvent; hot pressing is performed in a stainless steel mold at a temperature of 380°C, a pressure of 10MPa, and a holding time of 10min, and then cooled and demolded at room temperature to obtain a composite material block.

[0090] Comparative Example 1

[0091] The preparation steps of the carbon nanotube / polyetheretherketone composite material were the same as those in Example 1, except that the addition amount of the hydroxylated single-walled carbon nanotubes was 10%.

[0092] Comparative Example 2

[0093] The preparation steps of the carbon nanotube / polyetheretherketone composite material were the same as those in Example 1, except that the addition amount of the hydroxylated single-walled carbon nanotubes was 0%.

[0094] Comparative Example 3

[0095] A method for preparing a carbon nanotube / polyetheretherketone composite material, specifically comprising:

[0096] (1) Preparation of sulfonated polyetheretherketone:

[0097] 10g of polyetheretherketone was dissolved in 500ml of 98% concentrated sulfuric acid at 30°C, stirred for 48h, and then poured into 10 times the volume of ice water, stirred for 3h, and then allowed to stand for 36h. The precipitate was washed and filtered with deionized water several times until the pH value of the washing water solution was neutral. Finally, the precipitate was dried to obtain sulfonated polyetheretherketone.

[0098] (2) Preparation of carbon nanotube / polyetheretherketone composite materials:

[0099] The sulfonated PEEK powder is ultrasonically dispersed in anhydrous ethanol to fully infiltrate the sulfonated PEEK and then stirred to prepare a sulfonated PEEK suspension; 5% of unmodified single-walled carbon nanotubes are ultrasonically dispersed in anhydrous ethanol, and then the dispersion is dropped into the sulfonated PEEK suspension for premixing; the obtained mixed solution is dried at 150°C for 4h to remove the solvent; hot pressing is performed in a stainless steel mold at a temperature of 380°C, a pressure of 10MPa, and a holding time of 10min, and then cooled and demolded at room temperature to obtain a composite material block.

[0100] Comparative Example 4

[0101] A method for preparing a carbon nanotube / polyetheretherketone composite material, specifically comprising:

[0102] (1) Preparation of hydroxyl-modified single-walled carbon nanotubes:

[0103] The single-walled carbon nanotubes were added to 100 mL of a mixed solution (the volume ratio of H2O2 and concentrated sulfuric acid was 3:7) at 80°C, and stirred with a magnetic stirrer for 8 hours. After centrifugation, the solution was washed 5 times with distilled water, 3 times with ethanol, and dried at 80°C for 12 hours to obtain hydroxylated single-walled carbon nanotubes.

[0104] (2) Preparation of carbon nanotube / polyetheretherketone composite materials:

[0105] The unmodified PEEK powder is ultrasonically dispersed in anhydrous ethanol to fully infiltrate the sulfonated PEEK and then stirred to prepare a sulfonated PEEK suspension; 5% of hydroxylated single-walled carbon nanotubes are ultrasonically dispersed in anhydrous ethanol, and then the dispersion is dropped into the sulfonated PEEK suspension for premixing; the obtained mixed solution is dried at 150°C for 4h to remove the solvent; and hot pressing is performed in a stainless steel mold at a temperature of 380°C, a pressure of 10MPa, and a holding time of 10min, and then cooled and demolded at room temperature to obtain a composite material block.

[0106] The flexural strength of carbon nanotube / polyetheretherketone composites was tested.

[0107] The experimental results are shown in Table 1. Table 1 is as follows:

[0108]

[0109] It can be seen from Table 1 that in Examples 1-4, as the carbon nanotube content increases, the bending properties of the carbon nanotube / polyetheretherketone composite material gradually increase. When the carbon nanotube content is 5%, the bending properties of the material reach the maximum value; however, when the carbon nanotube content is 7%, the bending properties of the material decrease, indicating that too much carbon nanotube mass fraction will affect the bending strength of the material. The carbon nanotubes after hydroxylation can effectively enhance the mechanical properties of the material after chemical bonding with sulfonated polyetheretherketone. However, when the mass fraction of carbon nanotubes is 7%, the bending strength decreases instead. This is because too many carbon nanotubes are more difficult to disperse in polyetheretherketone, and the interface bonding ability with the resin decreases, thereby affecting the performance of the material. The introduction of carbon nanotubes increases the elastic modulus of the composite material and reduces its strength and elongation at break. In the polyetheretherketone composite material of comparative example 3, since the carbon nanotubes are not modified, the van der Waals force is large, resulting in serious agglomeration in the matrix, and the unmodified carbon nanotubes have poor compatibility with the polyetheretherketone matrix, which easily forms stress concentration points during the bending process, increases the brittleness of the material, and thus leads to a decrease in the overall mechanical properties of the material. The bending strength of the carbon nanotube / polyetheretherketone composite materials of comparative examples 1 to 4 is worse than that of example 3, indicating that the mechanical properties of the carbon nanotube / polyetheretherketone composite materials prepared by the present invention are better.

[0110] Cone calorimetry test of carbon nanotube / polyetheretherketone composites.

[0111] The experimental results are shown in Table 2. Table 2 is as follows

[0112]

[0113] Note: TTI is the ignition time, PHRR is the peak heat release rate, and FPI is the combustion performance index.

[0114] As shown in Table 2, with the increase of the content of single-walled carbon nanotubes, the peak heat release rate of the carbon nanotube / polyetheretherketone composite material is lower than that of pure polyetheretherketone, and has a longer ignition time, which indicates that the addition of single-walled carbon nanotubes effectively reduces the heat release rate of polyetheretherketone. Single-walled carbon nanotubes can form a protective layer due to their high regularity and degree of crystallinity, thereby effectively blocking the propagation of heat flow during the combustion process, reducing the combustion rate and peak heat release rate of the material. In addition, as a nanofiller, single-walled carbon nanotubes can enhance the function of the organic carbon layer, making it an effective heat transfer and mass transfer barrier, further hindering the propagation of heat. However, when the content of single-walled carbon nanotubes exceeds 7%, the peak heat release rate of the carbon nanotube / polyetheretherketone composite material is higher than that of pure polyetheretherketone, indicating that the single-walled carbon nanotubes fail to effectively enhance the flame retardant properties of polyetheretherketone at this time. This is because the addition of too much carbon nanotubes affects the interface bonding ability between carbon nanotubes and polyetheretherketone, making it difficult to disperse evenly and agglomerate, which is not conducive to the performance of the material, and ultimately makes the heat release rate higher than that of pure polyetheretherketone. The dielectric properties of Comparative Examples 1 to 4 are all worse than those of Example 4, which indicates that the carbon nanotube / polyetheretherketone composite material of the present invention has better flame retardant properties.

[0115] Figure 1 It shows that the single-walled carbon nanotubes after hydroxylation treatment are uniform in thickness, and many short tubes appear. The gaps between the carbon tubes are significantly reduced, and the carbon tubes are seriously adhered to each other. This is because hydroxyl functional groups are grafted on their surfaces, and hydrogen bonds are formed between the functional groups, which increases the surface electrostatic attraction and shortens the distance between the tubes.

[0116] Figure 2 The heat release rate curve refers to the heat released by the combustion of the material per unit time under the specified test conditions. The larger the HRR, the more heat is fed back to the surface of the material, resulting in faster pyrolysis of the material and more volatile combustibles, thereby accelerating the spread of the flame. Conversely, the smaller the HRR, the better the flame retardant effect of the material.

[0117] Figure 3 The residual carbon after the cone volume test is in a continuous and dense state. Such a carbon layer can effectively delay the transfer of heat and oxygen, reduce the thermal decomposition and diffusion rate of the material, and prevent the material from further burning.

[0118] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing a carbon nanotube / polyetheretherketone composite material, characterized in that: The following steps are involved: (1) Sulfonation of polyetheretherketone; (2) Hydroxyl-modified single-walled carbon nanotubes; (3) Synthesis of carbon nanotube / polyetheretherketone composites.

2. The method for preparing a carbon nanotube / polyetheretherketone composite material according to claim 1, characterized in that: The sulfonation treatment of the polyetheretherketone is as follows: after the polyetheretherketone is dissolved in concentrated sulfuric acid at 20-30° C. and stirred, the reaction solution is poured into a certain volume of ice water, stirred continuously for 2-3 hours, and then allowed to stand for 24-36 hours; then the precipitate is washed and filtered with deionized water for multiple times; finally, the precipitate is dried to obtain the sulfonated polyetheretherketone.

3. The method for preparing a carbon nanotube / polyetheretherketone composite material according to claim 2, characterized in that: The pH value of the washing water solution of the precipitate is neutral.

4. The method for preparing a carbon nanotube / polyetheretherketone composite material according to claim 2, characterized in that: The mass fraction of the concentrated sulfuric acid is 95% to 98%, and the stirring time is 24 to 76 hours.

5. The method for preparing a carbon nanotube / polyetheretherketone composite material according to claim 1, characterized in that: The hydroxyl-modified single-walled carbon nanotubes specifically comprise the following steps: adding the single-walled carbon nanotubes to 100 mL of a mixed solution at a temperature of 60 to 80° C., stirring with a magnetic stirrer for 6 to 10 hours; centrifuging and washing with distilled water for 3 to 5 times, washing with ethanol for 2 to 3 times, and drying at 80 to 100° C. for 12 hours to obtain hydroxylated single-walled carbon nanotubes.

6. The method for preparing a carbon nanotube / polyetheretherketone composite material according to claim 5, characterized in that: The mixed solution is a mixed solution of H2O2 and concentrated sulfuric acid in a volume ratio of 3:

7.

7. The method for preparing a carbon nanotube / polyetheretherketone composite material according to claim 1, characterized in that: The synthesis of the carbon nanotube / polyetheretherketone composite material specifically comprises the following steps: ultrasonically dispersing a certain amount of sulfonated PEEK powder in anhydrous ethanol to fully infiltrate the sulfonated PEEK and then stirring to prepare a sulfonated PEEK suspension; ultrasonically dispersing hydroxylated single-walled carbon nanotubes in anhydrous ethanol and then dropping the dispersion into the sulfonated PEEK suspension for premixing; drying the obtained mixed solution at 120-150° C. for 4-6 hours to remove the solvent; and hot pressing in a stainless steel mold and then cooling and demolding at room temperature to obtain a composite material block.

8. The method for preparing a carbon nanotube / polyetheretherketone composite material according to claim 7, characterized in that: The temperature of the hot pressing molding is 380-400° C., the pressure is 10-15 MPa, and the holding time is 10-20 min.

9. The method for preparing a carbon nanotube / polyetheretherketone composite material according to claim 7, characterized in that: The addition amount of the hydroxylated single-walled carbon nanotubes is 1%-7%.